2021
DOI: 10.1007/s40336-021-00445-w
|View full text |Cite
|
Sign up to set email alerts
|

State of the art of 18F-FDG PET/CT application in inflammation and infection: a guide for image acquisition and interpretation

Abstract: Aim The diagnosis, severity and extent of a sterile inflammation or a septic infection could be challenging since there is not one single test able to achieve an accurate diagnosis. The clinical use of 18F-fluorodeoxyglucose ([ 18 F]FDG) positron emission tomography/computed tomography (PET/CT) imaging in the assessment of inflammation and infection is increasing worldwide. The purpose of this paper is to achieve an Italian consensus document on [ 18 F]FDG PET/CT or PET/MRI in inflammatory and infectious disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 292 publications
(587 reference statements)
1
89
0
1
Order By: Relevance
“…Internists manage a wide variety of clinical issues, including fever of unknown origin (FUO) and inflammation of unknown origin (IUO). 18 F‐fluorodesoxyglucose positron emission tomography with computerized tomography ( 18 F‐FDG‐PET/CT) appears to be a high‐performance [1,2] and cost‐effective tool for diagnosing FUO [3]. IUO is defined as a prolonged and unexplained inflammatory syndrome for which final diagnoses are heterogeneous [4–6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internists manage a wide variety of clinical issues, including fever of unknown origin (FUO) and inflammation of unknown origin (IUO). 18 F‐fluorodesoxyglucose positron emission tomography with computerized tomography ( 18 F‐FDG‐PET/CT) appears to be a high‐performance [1,2] and cost‐effective tool for diagnosing FUO [3]. IUO is defined as a prolonged and unexplained inflammatory syndrome for which final diagnoses are heterogeneous [4–6].…”
Section: Introductionmentioning
confidence: 99%
“…is defined as a prolonged and unexplained inflammatory syndrome for which final diagnoses are heterogeneous [4][5][6]. Currently, 18 F-FDG-PET/CT is widely used in the diagnosis strategy for investigating IUO, but it is not yet clearly validated [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the biological distribution of 18 F-FDG, significant differences between the control mice and the mice at 4 h after infection were found in the lung and spleen at 15 min after 18 F-FDG administration ( Table 3 ). 18 F-FDG accumulation is reported to indicate areas of inflammation after infection, as well as bacterial infection [ 25 ]. The 18 F-FDG results of the present study suggested minimal areas of inflammation in the whole body because the accumulation of 18 F-FDG at 4 h after infection was not significantly different to that in controls, except in the brain and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…The urgency of imaging patients acutely ill with COVID-19 as well as following up post-COVID patients and those receiving vaccines, did not allow for time to create SARS-CoV-2 specific imaging agents. The domineering modality so far has been FDG-PET/CT covered in several excellent reviews (55,56) while SPECT imaging also contributes, for example, toward imaging of pulmonary emboli in COVID patients (57). As COVID-19 will gradually become endemic, it is only a matter of time when COVID-specific PET and SPECT imaging agents are developed.…”
Section: Imaging Of Viral Infectionsmentioning
confidence: 99%